Estudo de associação entre o transtorno bipolar e o gene da enzima triptofano hidroxilase 2 - Simone Becho de Campos (2009)
Bipolar disorder (BD) is a severe psychiatric illness characterized by the occurence of elevated mood alternating with depressive episodes. Lifetime prevalence for bipolar disorder type I is estimated from 0,4 to 1,6% using DSM-IV criteria for bipolar disorder. Disturbance of the central serotonergic system has been associated with the pathophysiology of affective disorders, suicidal behavior and panic disorder. Tryptophan hydroxylase 2 (TPH2) is a rate-limiting enzyme in serotonin synthesis and is considered an important candidate gene for psychiatric disorders. The aim of our study is to investigate a possible association between TPH2 gene polymorphisms and BD, suicidal behavior and panic disorder comorbidity susceptibility. Our sample consisted in 527 subjects (303 with a bipolar disorder diagnosis and 224 health controls) which were genotyped for eight TagSNPs (rs4448731, rs4565946, rs11179000, rs7955501, rs10506645, rs4760820, rs1487275 and rs10879357). Statistical analyses were performed by UNPHASED version 3.0.12 and Haploview. Single markers, genotype and haplotype association analysis did not show significant genetic association with bipolar disorder and suicidal behavior. However, we found a significant allele, genotype and haplotype associations with panic comorbidity in patientes with bipolar disorder and TPH2 gene variants. Our findings do not support the association between BD diagnosis, suicidal behavior and TPH2 polymorphisms, but suggest that polymorphisms in TPH2 gene may confer susceptibility to panic disorder comorbidity in patients with bipolar disorder. Further studiens are needed to replicate the positive association that we observed.